ANALISIS EFISIENSI PRODUKSI FRONTIER DAN PENDAPATAN USAHATANI KEDELAI SEKOLAH LAPANGAN PENGELOLAAN TANAMAN TERPADU (SL-PTT) DI KABUPATEN LAMPUNG SELATAN - Mesianna Marito Ambarita; Fembriarti Erry Prasmatiwi; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This study aimed to determine the technical efficiency of soybean farming, the factors that influence the technical efficiency of soybean farming, and to calculate the amount of the income of farmers in soybean farming in SLPTT of Candi  Puro Subdistrict of South Lampung regency.  The research location was selected on purpose (purposive sampling) by the consideration of that the area is a center of soybean production of SL-PTT. The samples number of farmers in the study were 55 farmers. Analyses were performed by using the frontier production function, multiple linear regression, and profit R/C. The results showed that  SL-PTT soybean farming in South Lampung regency was technically inefficient. Technical efficiency of farms in South Lampung regency that was equal to 68.17% and the majority of farmers in the range of 61-70% of technical efficiency. The factors that influenced the technical efficiency of the SL-PTT soybean farming in South Lampung regency were the scale of the business, costs of farming, and farm receipts.  SL-PTT soybean in South Lampung regency was profitable farming for farmers with income derived soybean farmer respondents soybean SLPTT per ha was over the cash cost of Rp6,319,193.50 and above the total revenue cost of Rp 5,565,571.96.  The R/C ratio was above 3.57 and the cash cost of the R/C ratio was 2.73 over the total cost. Key words: efficiency, frontier production, revenue, soybean